Architecture and Dynamics of the Jasmonic Acid Gene Regulatory Network. Issue 9 (21st August 2017) - Hickman, Richard; Van Verk, Marcel C.; Van Dijken, Anja J.H.; Mendes, Marciel Pereira; Vroegop-Vos, Irene A.; Caarls, Lotte; Steenbergen, Merel; Van der Nagel, Ivo; Wesselink, Gert Jan; Jironkin, Aleksey; Talbot, Adam; Rhodes, Johanna; et al.
Abstract : Detailed analysis of temporal reprogramming of gene activity illuminates the complexity of the jasmonic acid (JA) gene regulatory network and pinpoints transcriptional regulators of JA responses. Abstract: Jasmonic acid (JA ) is a critical hormonal regulator of plant growth and defense. To advance our understanding of the architecture and dynamic regulation of the JA gene regulatory network, we performed a high-resolution RNA-seq time series of methyl JA -treated Arabidopsis thaliana at 15 time points over a 16-h period. Computational analysis showed that methyl JA (MeJA ) induces a burst of transcriptional activity, generating diverse expression patterns over time that partition into distinct sectors of the JA response targeting specific biological processes. The presence of transcription factor (TF ) DNA binding motifs correlated with specific TF activity during temporal MeJA -induced transcriptional reprogramming. Insight into the underlying dynamic transcriptional regulation mechanisms was captured in a chronological model of the JA gene regulatory network. Several TFs, including MYB59 and bHLH27, were uncovered as early network components with a role in pathogen and insect resistance. Analysis of subnetworks surrounding the TFs ORA47, RAP2.6L, MYB59, and ANAC055, using transcriptome profiling of overexpressors and mutants, provided insights into their regulatory role in defined modules of the JA network. Collectively, our work illuminates the complexity of the JA gene regulatory network, pinpoints and validates previously unknown regulators, and provides a valuable resource for functional studies on JA signaling components in plant defense and development.